Radiative Feedback From Dry Environmental Air Accelerates Tropical Cyclogenesis - S.‐N. Wu; B. J. Soden (Geophysical Research Letters)
Abstract A number of recent studies have highlighted how radiative feedback from clouds accelerates tropical cyclone (TC) development by amplifying spatial gradients in radiative heating. This study extends this work by examining how spatial gradients in free tropospheric moisture influence TC development through their impact on environmental radiative heating. We conduct a series of idealized model experiments in which only the longwave radiative heating due to water vapor is modified in the environmental region outside of the TC area. These experiments demonstrate that a vortex in a drier environmental free troposphere experiences faster development. Moreover, weaker vortices actually require a dry environmental free troposphere to develop. The accelerated genesis mainly results from a stronger spatial gradient in moisture‐induced radiative heating, which enhances energy convergence through a stronger transverse circulation. These results highlight a potentially important and overlooked role of dry air in facilitating TC genesis.